Expression and Localization of Cathepsins B, D, and G in Dupuytren's Disease. Issue 2 (February 2018) - Tan, Kirin; Brasch, Helen D.; van Schaijik, Bede; Armstrong, James R.; Marsh, Reginald W.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte
Abstract : Background: The pathogenesis of Dupuytren's disease (DD) remains unclear. An embryonic stem cell (ESC)–like population in the endothelium of the microvessels around tissues that expresses components of the renin-angiotensin system (RAS) has been reported. This study investigated if this primitive population expresses cathepsins B, D, and G, that contribute to RAS bypass loops. Methods: 3, 3-Diaminobenzidine immunohistochemical (IHC) staining for cathepsins B, D, and G was performed on sections of formalin-fixed paraffin-embedded DD cords (n = 10) and nodules (n = 10). Immunofluorescence IHC staining was utilized to demonstrate co-expression of these cathepsins with ESC markers. Protein and gene expression of these cathepsins was investigated in snap-frozen DD cords (n = 3) and nodules (n = 3) by Western blotting and NanoString analysis, respectively. Enzymatic activity of these cathepsins was investigated by enzymatic activity assays. Results: 3, 3-Diaminobenzidine IHC staining demonstrated expression of cathepsins B, D, and G in DD cords and nodules. Gene expression of cathepsins B, D, and G was confirmed by NanoString analysis. Western blotting confirmed expression of cathepsins B and D, but not cathepsin G. Immunofluorescent IHC staining demonstrated high abundance of cathepsins B and D on the OCT4 + /angiotensin converting enzyme + endothelium and the smooth muscle layer of the microvessels. Cathepsin G was localized to trypase + cells within the stroma in DD cords and nodules with limited expression on the microvessels. Enzyme activity assays demonstrated functional activity of cathepsins B and D. Conclusions: Cathepsins B, D, and G were expressed in the DD tissues, with cathepsins B and D localized to the primitive population in the endothelium of the microvessels, whereas cathepsin G was localized to phenotypic mast cells, suggesting the presence of bypass loops for the RAS. Abstract : Supplemental Digital Content is available in the text.